'All these negative thoughts come flooding in': how young people with depression describe their experience of rumination. (23rd July 2015) - Oliver, Jeremy; Smith, Patrick; Leigh, Eleanor
Abstract: Rumination, or dwelling repeatedly on negative thoughts about the past, can prolong depression and make it worse. When treating clients with depression, it can be important to consider the behavioural, cognitive and emotional impact of rumination on their life. Previous research has examined adult experience of rumination, but the current study was the first to examine how young people with depression experience rumination. Seven young people with depression were interviewed about the cognitive content of their rumination episodes, the associated feelings, and any behavioural start and stop triggers. Interview transcripts were analysed using interpretative phenomenological analysis (IPA). Participants reported experiencing rumination as a disorientating cognitive battle, in which they felt under attack. The process elicited sadness predominantly, but also anger and anxiety, with mood and rumination often maintaining each other. Interpersonal interaction played a key role in starting and stopping rumination episodes. CBT-based interventions specifically targeting the ruminative process may be important for young people with depression, particularly interventions which consider the impact of family members or other systemic factors on rumination behaviour.